2020
DOI: 10.1088/1748-3190/ab6ca9
|View full text |Cite
|
Sign up to set email alerts
|

Optimization design of lightweight structure inspired by glass sponges (Porifera, Hexacinellida) and its mechanical properties

Abstract: The glass sponge is a porous lightweight structure in the deep sea. It has high toughness, high strength, and high stability. In this work, a super-depth-of-field microscope was employed to observe the microstructure of the glass sponge. Based on its morphological characteristics, two novel bio-inspired lightweight structures were proposed, and the finite-element analyses (FEA) of the structures were carried out under compression, torsion, and bending loads, respectively. The structure samples were fabricated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…One of the superior sources of inspiration in the development of novel 3D composites is the evolutionarily optimized 3D biosilica-based skeletons of glass sponges (Hexactinellida) [6,7] which represent a successful evolution in nature [8]. These hierarchically structured skeletons have been designed by living organisms over the last 600 Myr for efficient filtration of feed from surrounding seawater.…”
Section: Siliceous Skeletal Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the superior sources of inspiration in the development of novel 3D composites is the evolutionarily optimized 3D biosilica-based skeletons of glass sponges (Hexactinellida) [6,7] which represent a successful evolution in nature [8]. These hierarchically structured skeletons have been designed by living organisms over the last 600 Myr for efficient filtration of feed from surrounding seawater.…”
Section: Siliceous Skeletal Frameworkmentioning
confidence: 99%
“…For the first time, Brown et al [13] reported that 3D data extracted from the µCT of the sponge skeleton can be used to create accurate FE models and replication through 3D printing. Recently, based on morphological characteristics of glass sponges, two novel bio-inspired thin-walled lightweight structures were proposed and manufactured employing stereolithography 3D printing technology by Li et al [8]. Such proposed structures, inspired by glass sponges, can be used to create lighter structures with less material maintaining, however, exceptional mechanical properties, which has a great potential for the engineering applications, such as aerospace [8].…”
Section: Siliceous Skeletal Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Its wall thickness is usually 1-2 mm, while the longest can grow to *2 m. Researchers have found the excellent mechanical properties mainly come from its special cage-like skeleton, which is composed of vertical, horizontal, and diagonal struts. [28][29][30] In Li et al 31 two structures are proposed based on the morphological characteristics of glass sponges, and their bending stiffness is higher than the same weight honeycomb structure. In Fernandes et al 32 the diagonal reinforcement strategy of the glass sponge is optimized to achieve the highest buckling resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The structure is strong and flexible even though it is made of fragile glass. The reason is that the glass sponge has complex hierarchical and lightweight structures from nanometer to macroscopic length scales, and they have been evolving to overcome the brittleness of the glass material, which helps it achieve light weight combined with high strength [8]. material properties under a certain compression condition.…”
Section: Introductionmentioning
confidence: 99%